The Portrayal of Islamophobia in The Girl in the Tangerine Scarf - Haqqani, Ali Akbar; Sari, Dewi Puspita; Fadhli, Mochamad Ariq (Institut Agama Islam Negeri Kendari, 2023)
AbstractThe purpose of this study is to investigate the Islamophobia discourse, and to examine the cause and effect to the characters in the in the novel The Girl in the Tangerine Scarf. The study used qualitative approach and the results of this study are presented using a descriptive model. The case study approach was used in this study, and the theoretical framework which is used to analyzed the data was discourse anlaysis. The primary source of this study is Mohja Kahf’s novel entitled The Girl in the Tangerine Scarf, which was pulblished in. The study finds several portrayal of Islamophobia through the narative of the novel and the characters dialog and act. This study discovered that Islamophobia may put victims in very stressful situations and can cause them to undergo identity crisis.Keywords: Anti-Islam, Discourse, Islamphobia, The Girl in the Tangerine Scarf